ANSWER:
A. 28
Explanation:
Given:
m∠AFD = 90°
m∠AFB = 31°
From the graph, we can establish that ∠AFD is equal to the sum of angles ∠AFB, ∠CFB, and ∠CFD.
We can pose the following equation, knowing also that ∠AFB and ∠CFD are equal:
![\begin{gathered} \angle AFD=\angle AFB+\angle CFB+\angle CFD \\ \\ \angle AFB=\angle CFD,\text{ therefore:} \\ \\ \angle AFD=\angle AFB+\angle CFB+\angle AFB \\ \\ \angle AFD=2\cdot\angle AFB+\angle CFB \\ \\ \text{ We replacing:} \\ \\ 90\degree=2\cdot31\degree+\angle CFB \\ \\ \angle CFB=90\degree-2\cdot31\degree=90\degree-62\degree \\ \\ \angle CFB=28\degree \\ \\ \text{ and we know that the angle \angle CFB is equal to \angle DFE:} \\ \\ ∠DFE=\operatorname{\angle}CFB=28\operatorname{\degree} \end{gathered}]()
Therefore, the correct answer is A. 28